PERSEPSI GENERASI MUDA KALLAN BARU TERHADAP PENGGUNAAN PANTUN DALAM UPACARA PANGAKKASAN ADAT MAKKI: KAJIAN SOSIOLINGUISTIK - Natasia, Rosma; Djumingin, Sulastriningsih; Wijayanti, Tuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study used a descriptive qualitative method with the researcher as the main instrument and interviews as the data collection technique. The results of the study showed that the younger generation had a positive perception of the use of pantun in traditional ceremonies. This perception is reflected in two main findings, namely (a) pantun as a cultural identity, (b) a medium of traditional communication, and (c) pantun as a source of moral and educational values. The sociolinguistic study in this research also reveals the important role of language in the sustainability of the pantun tradition in the Pangakkasan Adat Makki ceremony. There are two main phenomena, namely language maintenance and language shift, which influence the level of understanding and involvement of the younger generation.